Comparison of image analysis and flow cytometric determination of cellular DNA content. Issue 2 (February 1991) - Cope, C; Rowe, D; Delbridge, L; Philips, J; Friedlander, M
Abstract : A good correlation (r = 0.94) was obtained between the DNA indices (DI) using flow cytometry and image analysis of nuclei cytospins extracted from paraffin wax embedded tumour sections. Some of the limitations and problems associated with image analysis which came to light included an unacceptably high coefficient of variation (CV) and a "left-shift" in the DI in most DNA histograms obtained when using image analysis of 5 microns sections. In contrast, the DNA histograms generated using image analysis of cytospun nuclei from paraffin wax blocks were of good quality and similar to those obtained using flow cytometry. Variability in Feulgen staining was common and an important source of error despite rigorous control of the staining technique. This could be overcome by using internal controls such as fibroblasts rather than external controls (rat hepatocytes) to determine the diploid DI with image analysis. A thorough understanding and appreciation of the methodological problems associated with image analysis and flow cytometric determination of DNA content is required before these methods find widespread clinical application.